IMPLEMENTASI DIVERSI DAN KEADILAN RESTORATIF DALAM PUTUSAN HAKIM: EVALUASI EMPIRIS PENERAPAN UU SPPA DI PENGADILAN NEGERI TASIKMALAYA - Hasby Ashidiqi, Muhamad; A. Arsyul Munir, Asep; Munir, Asep (Siyasyatuna | Jurnal Hukum Tata Negara, 2025)
This study aims to conduct a juridical analysis of judges' decisions regarding children in conflict with the law, based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA), with a case study of the Tasikmalaya District Court decisions from 2024 to 2025. The study evaluates the extent to which these decisions reflect the principles of SPPA, including restorative justice, child protection rights, and rehabilitative measures. Using a normative juridical method and descriptive qualitative approach, the research finds that although many decisions adhere to SPPA principles, challenges remain in fully implementing child rehabilitation and protection mechanisms. Long-term impact assessments reveal that the court's decisions do not yet comprehensively guarantee the full recovery and reintegration of the children involved.